Case Report of Isolated Gastric Metastasis of Pancreatic Cancer From a Diagnostic Biopsy: Management of a Rare Oncologic Entity. (26th February 2020) - Rothermel, Luke D.; Strosberg, Carolina; Centeno, Barbara A.; Malafa, Mokenge P.
Pancreatic ductal adenocarcinoma behaves aggressively, with surgically resectable disease having the best chance of long-term survival. Recurrence after surgery and adjuvant therapy is commonly due to distant metastatic disease and is typically managed with systemic therapies, not surgery. We present a rare case of an isolated gastric metastasis due to endoscopic ultrasound-guided with fine-needle aspiration (EUS-FNA) needle tract seeding that was managed surgically. Treatment was informed by input from a mutlidisciplinary team of medical, surgical, and radiation oncologists, radiologists, and pathologists. Rising carbohydrate antigen (CA)19-9 levels suggested disease recurrence, but the tumor's unusual location and slow growth made diagnosing the cause difficult, resulting in the late identification of the tumor. Palliative resection was performed, rending the patient with no evidence of disease followed by normalized CA19-9 levels. This case highlights the importance of multidisciplinary decision-making in detecting and treating the uncommon but significant tumor seeding with EUS-FNA biopsies in pancreatic ductal adenocarcinoma.